2014
DOI: 10.1590/1413-81232014195.21772013
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao excesso de peso em adultos usuários de restaurantes populares em Belo Horizonte, Brasil

Abstract: Fatores associados ao excesso de peso em adultos usuários de restaurantes populares em Belo Horizonte, BrasilFactors associated with being overweight among adults using low-budget restaurants in Belo Horizonte, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
0
0
3
Order By: Relevance
“…Segundo o estudo, a partir dos 40 anos a prevalência de excesso de peso esteve presente em maior frequência. Guimarães et al 19 e Machado et al 20 também encontraram dados semelhantes no que se refere ao aumento da idade ser diretamente proporcional a maiores chances de haver excesso de peso. O VIGITEL 17 também aponta que a prevalência de excesso de peso acompanha o aumento da idade.…”
Section: Discussionunclassified
“…Segundo o estudo, a partir dos 40 anos a prevalência de excesso de peso esteve presente em maior frequência. Guimarães et al 19 e Machado et al 20 também encontraram dados semelhantes no que se refere ao aumento da idade ser diretamente proporcional a maiores chances de haver excesso de peso. O VIGITEL 17 também aponta que a prevalência de excesso de peso acompanha o aumento da idade.…”
Section: Discussionunclassified
“…Quando nenhuma resposta foi positiva, o entrevistado foi classificado em situação de segurança alimentar nutricional (SAN); se a soma de pontos se encontrasse entre 1 e 5, classificou-se insegurança alimentar nutricional (IAN) leve; de 6 a 10, IAN moderada; e de 11 a 15, IAN grave 16,17 . Para as análises de fatores associados considerouse apenas SAN (escore 0) e IAN (escores de 1 a 15) 22 . Com relação aos problemas que afetam a vida dos idosos foi categorizado neste estudo as seguintes doenças: hipertensão, diabetes, outras doenças cardiovasculares tais como mobilidade/ dor.…”
Section: Variáveis Explicativasunclassified
“…The 19 studies, whose objective was to outline the profile of users, used analyzes of socioeconomic, sanitary, anthropometric and food indicators, as well as their level of food security [12,24,25,27,29,[31][32][33][34][35]37,39,41,42,44,45,[48][49][50]. Most studies identified the following users' profile: men, married, with or without children, with an educational level up to high school, and income mainly between half of the minimum wage and the minimum wage, with variations up to two times the minimum wage [12,24,25,27,31,32,34,35,41,44,45]. Still, five studies identified the prevalence of overweight and obesity in users, with percentages ranging between 42.9% and 53.2% [25,27,32,35,45].…”
Section: Popular Restaurants Users' Profilementioning
confidence: 99%
“…Most studies identified the following users' profile: men, married, with or without children, with an educational level up to high school, and income mainly between half of the minimum wage and the minimum wage, with variations up to two times the minimum wage [12,24,25,27,31,32,34,35,41,44,45]. Still, five studies identified the prevalence of overweight and obesity in users, with percentages ranging between 42.9% and 53.2% [25,27,32,35,45].…”
Section: Popular Restaurants Users' Profilementioning
confidence: 99%